Implementasi Internet of Thinks (IoT) Pada Pelacakan Posisi Tim Pencari SAR Kabupaten Sukoharjo Menggunakan LoRa - A Ari Andrianto (LPPM STIKI MALANG, 2024)
This research was motivated by communication problems and tracking the position of the SAR search team in Sukoharjo Regency, which was caused by limited connections and signals in remote areas. This limitation makes it difficult for the SAR command center to visually monitor the team's location on digital maps, thereby hampering the efficiency of search and rescue operations. The aim of this research is to implement Internet of Things (IoT) technology using LoRa to overcome these problems and increase the efficiency of search and rescue operations. The research method used is the prototyping paradigm, which involves developing and testing a prototype of an IoT-based tracking system. This prototype is designed to provide real-time location information for search teams, which can be accessed by the SAR command center even in areas with limited signal. The research results showed that the system developed was successful in providing real-time location information for the search team, which could be accessed by the SAR command center even though it was in an area with limited signal. In conclusion, this research succeeded in achieving its goal, namely improving the tracking and communication capabilities of SAR search teams in remote areas through the use of IoT and LoRa technology, so that it is hoped that it can increase the efficiency and effectiveness of search and rescue operations in the future.